Literasi Tentang Penyakit Menular Bagi Calon Pekerja Migran Indonesia di Luar Negeri Melalui Mekanisme OPP - Irfan Wahyudi; Rachmah Ida; Toetik Koesbandiarti; Sri Endah Kinasih; Delta Bayu Murti; Mochamad Kevin Romadhona (Journal of Urban Sociology, 2023)
Infectious diseases always go hand in hand with migration. Patterns of interaction and behavior in the process and during migration have consequences for disease transmission. Therefore, this research was conducted to determine literacy in infectious diseases for prospective Indonesian Migrant Workers. This research method uses descriptive with a qualitative approach. The research location was determined purposively, namely at the Technical Implementation Unit of the Indonesian Migrant Worker Protection Agency (UPT BP2MI) in the East Java Region. Data collection began with in-depth interviews of six people. Apart from in-depth interviews, they also conducted Focus Group Discussions (FGD) for PMI candidates who took part in the OPP. After the data is collected, and data analysis. The findings of this study resulted in prospective Indonesian Migrant Workers who go abroad do not understand the forms of disease transmission. The development of knowledge literacy on infectious diseases for PMI candidates is very weak due to Law Number 39 of 2004 and Law Number 18 of 2017, which have not fully provided protection in the health aspect on placement and post-placement, provision of materials on healthy lifestyles in order to prevention of disease transmission is still considered not very important for UPT BP2MI and UPT BP2MI lacks coordination with the East Java Provincial Health Office regarding OPP material. As a result, the literacy of prospective Indonesian Migrant Workers regarding disease transmission is very weak.Keywords: Indonesian Migrant Workers; Disease Transmission Literacy; Migration and Disease